Rural vs. urban disparities in association with lower urinary tract symptoms and benign prostatic hyperplasia in ageing men, NHANES 2001–2008. Issue 11 (28th July 2015) - Egan, K. B.; Suh, M.; Rosen, R. C.; Burnett, A. L.; Ni, X.; Wong, D. G.; McVary, K. T.
Summary: Objective: The objective of this study was to investigate rural/urban and socio‐demographic disparities in lower urinary tract symptoms and benign prostatic hyperplasia (LUTS/BPH) in a nationally representative population of men. Methods: Data on men age ≥40 years (N = 4, 492) in the 2001‐2008 National Health and Nutrition Examination Surveys were analysed. Self‐report of physician‐diagnosed enlarged prostate and/or BPH medication use defined recognised LUTS/BPH. Urinary symptoms without BPH diagnosis/medications defined unrecognised LUTS/BPH. Rural–Urban Commuting Area Codes assessed urbanisation. Unadjusted and multivariable associations (odds ratios (OR)) between LUTS/BPH and covariates were calculated using logistic regression. Results: Recognised and unrecognised LUTS/BPH weighted‐prevalence estimates were 16.5% and 9.6%. There were no significant associations between LUTS/BPH and rural/urban status. Significant predisposing factors for increased adjusted odds of recognised and unrecognised LUTS/BPH included age, hypertension (OR=1.4;1.4), analgesic use (OR=1.4;1.4) and PSA level >4 ng/mL (OR=2.3;1.9) when adjusted for rural/urban status, race, education, income, alcohol, health insurance, health care and proton pump inhibitor (PPI) use (all p ≤ 0.1). Restricting to urban men only (N = 3, 371), healthcare use (≥4visits/year) and PPI's increased adjusted odds of recognised LUTS/BPH (OR=2.0;1.6); no health insurance and <high school education decreased odds (OR=0.5;0.6) after adjusting for variables listed above, antidepressant and calcium channel blocker use (p ≤ 0.1). Also among urban men, adjusted odds of unrecognised LUTS/BPH increased for blacks (OR=1.9), Hispanic/Other (OR=1.9) and income<$34, 999 (OR=1.6). Among rural men only (N = 1, 121), adjusted odds of recognised and unrecognised LUTS/BPH increased for age, hypertension (OR=1.9;1.7) and analgesic use (OR=2.0;1.5) when adjusting for race, CRP, antidepressant and dyslipidaemic use (p ≤ 0.1). Conclusion: Rural/urban status was not associated with significantly increased adjusted odds of either recognised or unrecognised LUTS/BPH.